Knowledge regarding informed consent among surgical patients at Hospital Universiti Sains Malaysia (Hospital USM), Kubang Kerian, Kelantan - Hashim, Siti Noorain Mohd (Universiti Sains Malaysia, 2014)
Patients often feel powerless and vulnerable and it is a proven fact that patient’s awareness of legal and ethical issues related to the consent process is often limited. The goal of this descriptive cross-sectional study was to determine the level of knowledge regarding informed consent among surgical patients. This study also examined the differences of knowledge regarding informed consent with educational level, between male and female patients and also between frequencies of surgery. 112 surgical patients who were hospitalized in the five surgical wards Hospital USM were recruited in this study using purposive sampling. Data were collected from February to March 2014 using self-administered questionnaire and analyzed using SPSS version 20 for frequency, percentage, mean, standard deviation and p-value. Ethical approval was obtained from Research Ethics Committee (Human), USM. The results revealed overall level of knowledge regarding informed consent among surgical patients was at high level of knowledge (71.4%). However, surgical patients would like to have more information on information especially regarding any special precaution to be taken after operation, important risk and possible complication involved in having the operation and recurrence, any special dietary advice to be considered after operation, chance of successful result of the operation, for how much time operation will be done and the reason for operation. This study also found that there was significant differences of knowledge regarding informed consent with level of education (/?=0.046), no differences of knowledge between male and female (p=0.225), and frequency of surgeries that they had attend (p=0.500). As conclusion, surgical patients knowledge level regarding informed consent were highly satisfactory, however they need further understanding in certain information, thus the information’s will helps patients to cope with treatment and to achieve better surgical outcome.